Analisis Kebijakan PHK pada UU Cipta Kerja dalam Perspektif Teori Konflik Karl Marx: Analysis of Layoff Policy in the Job Creation Law through the Perspective of Karl Marx’s Conflict Theory - Alvares Richie Putra; Sulismadi Sulismadi (Anterior Jurnal, 2026)
This study aims to analyze the layoff policy (PHK) within Indonesia's Job Creation Law No. 11 of 2020 through the perspective of Karl Marx's conflict theory. The layoff policy is a crucial issue in labor relations as it directly affects workers' welfare and social stability. The Job Creation Law provides greater flexibility for employers to terminate employment, but this has sparked debate over the perceived weakening of workers' bargaining power. This research employs a qualitative approach using a library research method, collecting data from academic literature, legislation, and related scholarly journals. The findings reveal that the layoff policy in the Job Creation Law reflects capitalist class domination over the working class, as Karl Marx's conflict theory explains. The imbalance between employers and workers is reinforced by state intervention that tends to side with capital owners. The study concludes that Indonesia's labor policies remain oriented toward economic efficiency rather than social justice for workers.